2023
DOI: 10.1161/hypertensionaha.122.20853
|View full text |Cite
|
Sign up to set email alerts
|

Catheter-Based Renal Denervation: 9-Year Follow-Up Data on Safety and Blood Pressure Reduction in Patients With Resistant Hypertension

Abstract: BACKGROUND: Recent sham-controlled randomized clinical trials have confirmed the safety and efficacy of catheter-based renal denervation (RDN). Long-term safety and efficacy data beyond 3 years are scarce. Here, we report on outcomes after RDN in a cohort of patients with resistant hypertension with an average of ≈9-year follow-up (FU). METHODS: We recruited patients with resistant hypertension who were previously enrolled in various RDN trials applying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 33 publications
(44 reference statements)
1
29
1
1
Order By: Relevance
“…This becomes more unlikely when we consider the substantial blood pressure lowering effects across all SSI risk classes. Moreover, while across this cohort a total reduction in antihypertensive load was evident [31], we show here significant reduction in beta blocker DDDs only in the moderate group at long-term follow-up. With the chronotropic effects of beta blockers, their effect on HR and thus SSI Risk is evident.…”
Section: Renal Sodium Handling: Potential Confoundercontrasting
confidence: 45%
“…This becomes more unlikely when we consider the substantial blood pressure lowering effects across all SSI risk classes. Moreover, while across this cohort a total reduction in antihypertensive load was evident [31], we show here significant reduction in beta blocker DDDs only in the moderate group at long-term follow-up. With the chronotropic effects of beta blockers, their effect on HR and thus SSI Risk is evident.…”
Section: Renal Sodium Handling: Potential Confoundercontrasting
confidence: 45%
“…23 In a recent cohort study of 66 patients, RDN had a consistent benefit over a 9-year follow-up without adversely affecting kidney function. 24 Previous meta-analyses of RCTs showed significant benefits of RDN over sham procedures in reducing AMB and daytime BP. 25,26 In a sub-analysis of patients with resistant HTN, Ahmed et al 27 found no significant difference between RDN and sham with respect to 24 h AMB systolic and diastolic BP.…”
Section: Discussionmentioning
confidence: 99%
“…Still, a question of the long‐term sustainability of the benefit of RDN remains, especially with respect to any new adverse outcomes 23 . In a recent cohort study of 66 patients, RDN had a consistent benefit over a 9‐year follow‐up without adversely affecting kidney function 24 …”
Section: Discussionmentioning
confidence: 99%
“…60 In Dahl-SS rats, during the early period, renal denervation does not decrease BP, 61 and increased sympathetic activity is not observed upon salt-induced hypertension, 62 although the Dahl-SS rats at 4 to 8 weeks with chronic kidney disease showed increased renal sympathetic activity and significant BP reduction by renal denervation, indicating heterogeneity in the pathophysiology of SS-HT. Notably, renal denervation has been proven in many trials to lower BP in patients with hypertension, 63 and in 2023, the Food and Drug Administration approved renal denervation with specific types of devices. However, the impact of renal denervation on SSBP in humans remains to be resolved.…”
Section: Renal Sympathetic Nervous System In Ss-htmentioning
confidence: 99%